Keahlian, Indepedensi, Kepatuhan Pada Kode Etik, Motivasi, Dan Kualitas Auditor Pada Inspektorat Pengawasan Keuangan Daerah Kabupaten Bogor - Amin Mangamis (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2017)
The research objective to identify, analyze and obtain empirical evidence on the Influence of expertise, independence, adherence to a code of ethics and motivation partially and simultaneously to the quality of auditors on Financial Oversight Inspectorate Bogor regency. The method used was survey by using instrument in the form of a questionnaire with Likert scale model. The population in this study were all officers of Regional Financial Oversight Inspectorate Bogor District who participated in the task of inspection, as many as 60 people. From the research results obtained: Skills significant effect on the quality of auditors. The independence of a significant effect on the quality of auditors. Compliance with the code of conduct a significant effect on the quality of auditors. Motivation significant effect on the quality of auditors. Expertise, Independence, Compliance with the code of ethics and motivation simultaneous effect on the quality of the auditor, the better the expertise plus good independence and has adherence to a code of ethics, the better the quality auditor.